Efektifitas Permainan Bentengan terhadap Perkembangan Sosial Anak di Taman Kanak-kanak Jannatul Ma’wa Padang - Fitri, Deni Winda; Wirman, Asdi (Jurnal Caksana : Pendidikan Anak Usia Dini, 2019)
Abstract This study aims to find out how much effectiveness the game against the social development of children in Jannatul Ma'wa Padang Kindergarten. The research begins with the assumption that social development can be done through playing games. Children do not want to work with friends and prefer to do activities individually. Even to reduce those who still like to disturb their friends while following the learning process. This study is a quantitative approach with an experimental type of quasy. The population of children in Jannatul Ma’wa Padang Kindergarten. The sampling technique was purposive sampling, finally obtained samples of classes B1 and B2, each of which amounted to 12 children. The average social ability achieved by children in the experimental class was 80,56 and the control class with an average of 71,53. While the effect size with cohen's d is 1,09>0,80. These results can be concluded that the bentengan game effectively develops the social skills of children in Jannatul Ma’wa Padang Kindergarten.